1992
DOI: 10.1136/adc.67.6.712
|View full text |Cite
|
Sign up to set email alerts
|

Dysmorphic features in offspring of alcoholic mothers.

Abstract: The frequencies of 60 minor physical anomalies and various craniofacial measurements in 52 children with alcohol exposure of various durations in utero were determined and compared with 48 non-exposed healthy children at a mean age of 27 months. Compared with nonexposed children a significantly higher total minor physical anomaly count was observed in those children exposed prenatally to alcohol throughout pregnancy. Binge drinking was not associated with an increased minor physical anomaly count. During the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 28 publications
0
15
1
1
Order By: Relevance
“…Studies with both positive and negative results are reported. 8,12,14 Although among women who drank moderately we found a significant association between binge drinking and their children's risk of renal agenesis or hypoplasia, we cannot interpret this finding with the available data.…”
Section: Discussionmentioning
confidence: 71%
“…Studies with both positive and negative results are reported. 8,12,14 Although among women who drank moderately we found a significant association between binge drinking and their children's risk of renal agenesis or hypoplasia, we cannot interpret this finding with the available data.…”
Section: Discussionmentioning
confidence: 71%
“…One could speculate that the intellectual problems in MPKU offspring could be similar in origin to those seen in the fetal alcohol syndrome since increased blood Phe during pregnancy has resulted in offspring facial dysmorphology [ 19] similar to that observed in fetal alcohol syndrome [2,3] and congenital pyruvate dehydrogenase deficiency [ 18]. Phenylpyruvate (a byproduct of Phe metabolism) and acetaldehyde (a byproduct of alcohol metabolism) are both potent inhibitors of pyruvate dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical features are identical to those of the foetal alcohol syndrome (Clarren & Smith, 1978;Autti-Ramo et al, 1992) and, in fact, may be due to the same mechanism -interference with the activity of pyruvate dehydrogenase (Robinson, 1987;Hard, 2001). Numerous reviews have been published (Hanley et al, 1987) since the problem of MPKU was initially raised in 1963 by Mabry (Mabry et al, 1963).…”
Section: Maternal Pku (Mpku)mentioning
confidence: 76%